THE RELATIONSHIP BETWEEN SUSTAINABLE LEADERSHIP AND SUSTAINABLE HUMAN RESOURCE MANAGEMENT PRACTICES - Nabhani; Mansur Anakampun; Sunardi Siregar; Rakesh Sitepu; Anggia Sari Lubis (International Conference on Health Science, Green Economics, Educational Review and Technology, 2025)
Sustainable leadership has gained increasing attention as organizations seek to balance economic performance with social and environmental responsibilities. This study examines the relationship between sustainable leadership and sustainable human resource management (HRM) practices. Drawing on the sustainability and leadership literature, this research investigates how leaders who emphasize long-term value creation, ethical behavior, and stakeholder engagement influence the adoption of sustainable HRM practices, including employee development, well-being, fairness, and environmental responsibility. Using a quantitative research design, data were collected from employees across various organizations and analyzed using statistical techniques to test the proposed relationships. The findings indicate that sustainable leadership has a significant and positive effect on sustainable HRM practices. Leaders who demonstrate sustainability-oriented values and behaviors are more likely to foster HRM practices that support employee sustainability and organizational resilience. This study contributes to the growing body of literature on sustainability by highlighting the critical role of leadership in promoting sustainable HRM practices. Practically, the results suggest that organizations should develop sustainable leadership competencies to strengthen their human resource strategies and achieve long-term sustainability goals..